Does Government Regulation No. 20 of 2015 Affect Auditor Independence? - Widiatami, Anna Kania; Solikhah, Badingatus; Aeni, Ida Nur (Jurnal Reviu Akuntansi dan Keuangan)
This study aims to investigate whether the Government Regulations No 20 the Year 2015 regarding the rotation of auditors will affect auditor independence. This study conducted observations on mining companies listed on the IDX by dividing into two observation periods, namely before and after the regulations applied. The results showed no change in auditors' independence to issue going concern audit opinions influenced by Audit Firm (AF) tenure. Both before and after the regulations applied. However, there are changes in audit partner (AP) tenure in influencing auditor independence before and after the regulations applied. The article suggests that audit partner supervision by authorities and professional associations needs to be improved based on the results of the study. It includes increasing supervision and supervision from Audit Firm leaders on all audit teams in the field, from junior auditors and senior auditors to in-charge managers.